Daily News: Bicentennial tremor - government donates $500,000 - Pryor, Geoff, 1944- (1985)
A question of relativities. The Hawke Government announces a $750,000 grant to help the victims of the disastrous Mexican earthquake. It is also revealed that the chief executive of the Australian Bicentennial Authority, Dr. David Armstrong is pressed by Prime Minister Hawke to resign his position and receives a golden handshake of $504,000. --Information supplied by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 24 September 1985.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Australian Bicentenary, 1988 -- Caricatures and cartoons; Earthquakes -- Mexico -- Caricatures and cartoons; Australia -- Politics and government -- 1976-1990 -- Caricatures and cartoons; Australia -- Foreign relations -- 1976-1990 -- Caricatures and cartoons; Australia -- Economic policy -- 1976-1990 -- Caricatures and cartoons